2012
DOI: 10.7166/21-2-54
|View full text |Cite
|
Sign up to set email alerts
|

Demand Categorisation, Forecasting, and Inventory Control for Intermittent Demand Items

Abstract: This paper considers the bi-criteria scheduling problem of simultaneously minimising the total completion time and the number of tardy jobs with release dates on a single machine. Since the problem had been classified as NP-Hard, two heuristics (HR9 and HR10) were proposed for solving this problem. Performance evaluations of the proposed heuristics and selected solution methods (HR7 and BB) from the literature were carried out on 1,100 randomly generated problems ranging from 3 to 500 jobs. Experiment results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
0
7
1
2
Order By: Relevance
“…Our work contributes to the growing body of literature reviews on spare part demand forecasting along the following lines. Babiloni et al (2010) provide a review on intermittent demand forecasting, whereas Boylan & Syntetos (2010), Rego & Mesquita (2011), and Bacchetti & Saccani (2012) review the literature on spare parts demand forecasting specifically. The focus mainly lies on techniques based on historical demand data, and the authors hardly consider other sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…Our work contributes to the growing body of literature reviews on spare part demand forecasting along the following lines. Babiloni et al (2010) provide a review on intermittent demand forecasting, whereas Boylan & Syntetos (2010), Rego & Mesquita (2011), and Bacchetti & Saccani (2012) review the literature on spare parts demand forecasting specifically. The focus mainly lies on techniques based on historical demand data, and the authors hardly consider other sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…Its core idea is to calculate the number of periods with 0 demand in the analyzed timeframe and build in an additional smoothing equation. The mathematical-statistical description (Babiloni et al, 2010;Boylan et al, 2008) can be found in the work of Croston published in 1972. Syntetos and Boylan have pointed out, however, that the Croston method results in biased estimation.…”
Section: Forecasting Of Sporadic Demandmentioning
confidence: 99%
“…According to Boylan et al (2008) and Babiloni et al (2010) different product categories require different forecasting methods to be used. Where demand volume variation (that is CV DE ) is over 0.7 and/or the sporadicity of a product are high (value of p is higher than 1.32), the recommended forecasting method is the Syntetos-Boylan method.…”
Section: Forecasting Of Sporadic Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…Para este fin son calculados dos indicadores: un Coeficiente de Variación Cuadrática (CV2), y el Promedio del Intervalo entre Demandas (ADI). Este último valor puede ser clasificado en otros cuatro grupos: i) errática, cuando el tamaño de la demanda presenta elevada variabilidad; ii) intermitente, cuando la serie presenta varios valores nulos de demanda; iii) granulada ó irregular (en la literatura es conocida como lumpy) cuando la variabilidad del tamaño de la demanda y los períodos entre dos demandas no nulas son altos; y iv) atenuada, cuando la variabilidad del tamaño de la demanda y el período entre dos demandas no nulas son bajas [3][4][5]. La …”
Section: Métodos De Previsión De Demanda Intermitenteunclassified